Bibliometric analysis of jurnal SPORTIF: jurnal penelitian pembelajaran - Hanief, Yulingga Nanda (Universitas Nusantara PGRI Kediri, 2021)
Research using bibliometric analysis methods in sports journals has never been done, especially in accredited national journals. This study evaluates the pattern and development of publications in the Jurnal SPORTIF: Jurnal Penelitian Pembelajaran from 2015 to 2020. This study uses bibliometric analysis and visualization of similarities using the VOSViewer application for the graphical conception of bibliographic data such as co-occurrence of keywords and co-authorship. Also, this study will also evaluate the most productive institutions, the most productive authors, the most cited articles, the number of citations, and the level of author collaboration. The analysis results show an increase in publication production after the Jurnal SPORTIF: Jurnal Penelitian Pembelajaran was declared accredited by SINTA 2 in 2018, which shows an increase in interest in submitting articles. Forming basic movements in elementary school students through traditional games is one of the currently trending topics, so there are gaps and opportunities to exploit research with this theme. Universitas Nusantara PGRI Kediri is the most productive institution with 29 articles, while the most productive writer is Budiman Agung Pratama, with five articles published so far. Further research is expected to compare the pattern and development of publications in the SINTA 2 national accredited journals.